Face-to-face training on climate services reaches 106,000 farmers in Rwanda - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
The Rwanda Climate Services for Agriculture project supported the Twigire Muhinzi agricultural extension service to scale up the Participatory Integrated Climate Services for Agriculture (PICSA) approach in 27 of Rwanda’s 30 districts, facilitating 106,000 Rwandan farmers to understand and act on climate information.